Proceedings of the International symposium on frontiers in science : on the occasion of the 65th birthday of Professor Hans Frauenfelder, Urbana, Il 1987 - International Symposium on Frontiers in Science (1987 : Urbana, Illinois, United States); Frauenfelder, Hans; Chan, Shirley S.; Debrunner, Peter G. (New York : American Institute of Physics, 1988)
40